Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd009109.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Single crowns versus conventional fillings for the restoration of root filled teeth

Abstract: Comparison 1 Composite + crown versus composite only, Outcome 2 All years, failure of post (noncatastrophic).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 24 publications
0
30
1
1
Order By: Relevance
“…1,9 Two systematic reviews available in the literature show that there is no evidence to support the "best way" to restore endodontically treated teeth. 20,21 A recent study comparing the use of glass fiber posts versus cast metal posts, in teeth with no remaining coronal wall, showed that no difference was found between the groups using these two types of posts, after up to 3 years of follow-up. 5 However, several factors must be borne in mind when choosing the post to be used in restoring ETT, including remaining coronal structure, presence of ferrule and post material.…”
Section: Discussionmentioning
confidence: 99%
“…1,9 Two systematic reviews available in the literature show that there is no evidence to support the "best way" to restore endodontically treated teeth. 20,21 A recent study comparing the use of glass fiber posts versus cast metal posts, in teeth with no remaining coronal wall, showed that no difference was found between the groups using these two types of posts, after up to 3 years of follow-up. 5 However, several factors must be borne in mind when choosing the post to be used in restoring ETT, including remaining coronal structure, presence of ferrule and post material.…”
Section: Discussionmentioning
confidence: 99%
“…A crown is generally superior to intracoronal restorations, but it is more expensive, its preparation is more time consuming, and it removes more tooth structure than intracoronal restorations (Fedorowicz et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…The role of endodontic post is to retain the core material only 7 . 2mm of ferrule is necessary for the tooth restoration with crown [7][8]9,10 . Mechanical stress should be taken under consideration while restoring ETT either anterior or posterior teeth 10,[11][12] .…”
Section: Discussionmentioning
confidence: 99%
“…It is very important to select which restoration is more suitable for a particular case. There is a variety of restorative materials available such as amalgams, composites, Glass Ionomers and Resin modified GIC which are mostly used directly [6][7][8] . The indirect restorative options could be Ceramics, Metal ceramics, cast gold alloys and base metal alloys which are fabricated in the dental laboratory and cemented 9 .…”
Section: Introductionmentioning
confidence: 99%